Uneven understanding of morphological impacts of dams: upstream vs. downstream - Khaleghi, Somaiyeh; Nosrati, Kazem (Frontiers in Environmental Science, 2025)
Despite the extensive knowledge on dam-induced river adjustments, systematic comparisons and integrated syntheses of both upstream and downstream morphological effects are still lacking. In this study, we systematically reviewed all available studies on these adjustments from the SCOPUS and WOS databases. We found that the majority of the 95 analyzed papers (80%) focused exclusively on downstream river channel changes, such as channel incision and narrowing. In contrast, upstream adjustments, including channel widening and aggradation, were addressed in only 16% of the articles, and their associated ecological impacts remain largely understudied. Most of the reviewed studies used remote sensing methods to analyze river morphological adjustments in temperate climates and single-thread rivers. This review highlights the limited understanding of river morphological changes occurring upstream from dams and their ecological consequences. Addressing this gap in further research is crucial for informing future river management practices aimed at mitigating the impacts of dams.